Stability of the World Trade Web over time – An extinction analysis - Foti, Nicholas J.; Pauls, Scott; Rockmore, Daniel N. (Journal of economic dynamics & control, 2013)
The World Trade Web (WTW) is a weighted network whose nodes correspond to countries while edge weights reflecting the value of imports and/or exports between countries. In this paper we introduce to this macroeconomic system the notion of extinction analysis, a technique often used in the analysis of ecosystems, for the purpose of investigating the robustness of this network. In particular, we subject the WTW to a principled set of in silico “knockout experiments,” akin to those carried out in the investigation of food webs, but suitably adapted to this macroeconomic network. Informed by results in network theory as well as studies of contagion in economic networks, we seek to understand the role of connectance in the robustness of the system. We interpret increasing connectance as one aspect of a move towards globalization and liberalized trade policy. Broadly, our experiments confirm two conjectures. First, that the WTWs are “robust yet fragile” networks — robust to random failures but fragile under targeted attack. Second, that growing connectance has both positive and negative impacts on robustness. More specifically, we find that increasing connectance corresponds to increasing robustness for small shocks but to decreasing robustness in the face of large, cascading shocks up to the system. This yields evidence in support of the view that globalization, as witnessed by increasing connectance, increases the ability of a system to absorb shock up until a certain size, whereupon the shock overwhelms the system and sparks a broader contagion. We anticipate that experiments and measures like these can play an important role in the evaluation of the stability of economic systems.